Comparative geographical analysis of foreign trade in goods of Belarusian and Russian regions (by the example of Gomel oblast and the Republic of Bashkortostan) - Zakirov, Ilnur V.; Shavel, Aliaksei N. (Journal of the Belarusian State University. Geography and Geology, 2017)
The article gives a comparative geographical analysis of the territorial and structural features of foreign trade of Gomel oblast and the Republic of Bashkortostan for 2005–2015 in the context of the global economic crisis and regional integration within the Customs Union, the Common Economic Space and the Eurasian Economic Union. The methodology of comparative geographical analysis of region foreign trade is grounded. It involves the assessing of overall foreign trade indicators (export, import, balance), the definition of its commodity and geographical structure features by using Herfindahl – Hirschman index (IHH ) of concentration and Riabtsev’s index (IR ) of structural shifts and the selection of proposals for the foreign trade optimization. It has been identified the factors of development, diversification and dynamics of commodity and geographical structure and highlights similarities and differences in foreign trade of Gomel oblast and the Republic of Bashkortostan. The developed methodology can be used for comparative geographical study offoreign trade of the countries and regions. Received results and elaborated proposals necessary for making management decisions to the optimization of foreign trade activity of the Gomel oblast and the Republic of Bashkortostan.
Keywords: foreign trade; export; import; balance; comparative geographical analysis; Gomel oblast; Republic of Bashkortostan; commodity and geographical structure; Herfindahl – Hirschman index; Riabtsev index